The Characteristics of Hierarchy of Self-Image Components Depending on Social And Cultural Affiliation - Yanitskiy, M; Seryy, A; Braun, O (KnE Life Sciences, 2018)
In accordance with the methodology of the constructivist approach, the personal identity manifested as a unique self-image is regarded as a dynamic hierarchical system. Under that approach, based on M. Kuhn and T. McPartland’s test, we have developed and put into practice a special questionnaire, which allows ranking 16 categories in terms of their importance. These categories reflect social role components of self-image in the main spheres of life, thus presenting an individual or a group identity structure as an orderly hierarchy. Based on a sample of 1251 students of various sex, age, nationality, confession, residence and field of study, we have proved that affiliation to a certain social or cultural group influences the hierarchy of self-image components. The study has shown that of the highest impact on the significance of self-image components is gender and professional affiliation, and, albeit less substantial, belonging to a particular ethnoreligious group and being the resident of a certain region. Sociocultural affiliation in all instances was an important differentiating characteristic, which determined the disparities in significance of the respective basis of the identity in the hierarchy. At the same time, sociocultural affiliation in most cases had an effect on the importance of less than a half of the other self-image components, thus determining the general structure of the identity. In conclusion, gender, educational and professional, ethnic, confessional or regional sociocultural group is a significant social determinant of personal development in the formation of the self-image hierarchy, which underlies the characteristics and structure of one’s identity. Keywords: identity, self-image, sociocultural environment, youth, students.